Realist evaluation of the role of the Universal Health Coverage Partnership in strengthening policy dialogue for health planning and financing: a protocol. Issue 1 (17th January 2019) - Robert, Emilie; Ridde, Valery; Rajan, Dheepa; Sam, Omar; Dravé, Mamadou; Porignon, Denis
Abstract : Introduction: In 2011, WHO, the European Union and Luxembourg entered into a collaborative agreement to support policy dialogue for health planning and financing; these were acknowledged as core areas in need of targeted support in countries' quest towards universal health coverage (UHC). Entitled 'Universal Health Coverage Partnership', this intervention is intended to strengthen countries' capacity to develop, negotiate, implement, monitor and evaluate robust and integrated national health policies oriented towards UHC. It is a complex intervention involving a multitude of actors working on a significant number of remarkably diverse activities in different countries. Methods and analysis: The researchers will conduct a realist evaluation to answer the following question: How, in what contexts, and triggering what mechanisms, does the Partnership support policy dialogue for health planning and financing towards UHC? A qualitative multiple case study will be undertaken in Togo, Liberia, Democratic Republic of Congo, Cape Verde, Burkina Faso and Niger. Three steps will be implemented: (1) formulating context–mechanism–outcome explanatory propositions to guide data collection, based on expert knowledge and theoretical literature; (2) collecting empirical data through semistructured interviews with key informants and observations of key events, and analysing data; (3) specifying the intervention theory. Ethics and dissemination: The primary target audiences are WHO and its partner countries; international and national stakeholders involved in or supporting policy dialogues in the health sector, especially in low-income countries; and researchers with interest in UHC, policy dialogue, evaluation research and/or realist evaluation.